Comprehensive insight into anti-staphylococcal and anti-enterococcal action of brominated and chlorinated pyrazine-based chalcones - Konečná, Klára; Diepoltová, Adéla; Holmanová, Pavlína; Jand’ourek, Ondřej; Vejsová, Marcela; Voxová, Barbora; Bárta, Pavel; Maixnerová, Jana; Trejtnar, František; Kučerová-Chlupáčová, Marta (Frontiers in Microbiology, 2022)
The greatest threat and medicinal impact within gram-positive pathogens are posed by two bacterial 21 genera, Staphylococcus and Enterococcus. Chalcones have a wide range of biological activities and 22 are recognized as effective templates in medicinal chemistry. This study provides comprehensive 23 insight into the anti-staphylococcal and anti-enterococcal activities of two recently published 24 brominated and chlorinated pyrazine-based chalcones, CH-0y and CH-0w. Their effects against 4 25 reference and 12 staphylococcal and enterococcal clinical isolates were evaluated. Bactericidal 26 action, the activity in combination with selected conventional antibiotics, the study of post-27 antimicrobial effect (PAE, PAE/SME), and in vitro and in vivo toxicity, were included. In CH-0y, 28 anti-staphylococcal activity ranging from MIC = 15.625 to 62.5 μM, and activity against E. faecium 29 from 31.25 to 62.5 μM was determined. In CH-0w, anti-staphylococcal activity ranging from 31.25 30 to 125 μM, and activity against E. faecium and E. faecalis (62.5 μM) was revealed. Both CH-0y and 31 CH-0w showed bactericidal action, beneficial impact on bacterial growth delay within PAE and 32 PAE/SME studies, and non/low toxicity in vivo. Compared to CH-0w, CH-0y seems to have higher 33 anti-staphylococcal and less toxic potential. In conclusion, chalcones CH-0y and CH-0w could be 34 considered as structural pattern for future adjuvants to selected antibiotic drugs.